2022
DOI: 10.1021/acsmaterialslett.2c00661
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-Enhanced Emission in a Red Cu(I) Emitter with Quantum Yield >99%

Abstract: It is a significant challenge to achieve a high photoluminescence quantum yield of Cu(I) complexes, particularly for red Cu(I) emitters, because of their considerable reorganization energy and weak spin−orbit coupling. Herein, we report a red phosphorescent cyclic trinuclear Cu(I) complex (denoted as 1), which was formed by reacting alkyl-substituted pyrazole ligands (4-isobutyl-3,5-dimethyl-1H-pyrazole) with in situ generated Cu(I) ions. Complex 1 was nonemissive in a pure tetrahydrofuran (THF) solution, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…The higher-energy absorptions below 350 nm are typical for ligand-centered [π → π*] (dppy ligand) absorption, based on the similar absorption energies with those of the free dppy ligand. The lower-energy shoulder is similar to that observed in the related Cu 3 H and Cu 4 H , , suggesting their origin from ligand-to-metal-metal charge transfer (LMMCT) or cluster-centered (CC).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The higher-energy absorptions below 350 nm are typical for ligand-centered [π → π*] (dppy ligand) absorption, based on the similar absorption energies with those of the free dppy ligand. The lower-energy shoulder is similar to that observed in the related Cu 3 H and Cu 4 H , , suggesting their origin from ligand-to-metal-metal charge transfer (LMMCT) or cluster-centered (CC).…”
Section: Resultssupporting
confidence: 56%
“…Comparing the emissions both in the solid state and in solution, a red shift in energy is observed on going from Cu 7 H 5 to Cu 8 H 6 and Cu 12 H 9 (Figure S13), which is consistent with the order of the stronger cuprophilic interactions by single-crystal X-ray analysis. Following previous assignments , and in view of the good σ-donating capability of the dppy ligand, the origin of the emissions for three Cu­(I)H clusters is assigned as the triplet ligand-to-metal-metal charge-transfer ( 3 LMMCT) excited state or cluster-centered (CC) modified by metal–metal interactions. The red shift in the emission wavelengths of Cu 7 H 5 to Cu 8 H 6 and Cu 12 H 9 may be ascribed to the stronger cuprophilic interactions, which decreases the energy of the metal-centered acceptor orbitals and gives rise to a lower LMMCT or CC emission energy.…”
Section: Resultsmentioning
confidence: 92%
“…(iii) In zone C (70% < WC < 90%), the clustered molecules are tightly packed, thus suppressing the molecular motion and vibration to enhance luminescence ( Figure 3 h(ii)). Very recently, the Li group also discovered the AIE phenomenon in Cu(I)-based cyclic trinuclear complexes (Cu(I)-CTC) [ 29 ]. These NCs exhibit no photoluminescence in pure tetrahydrofuran until water is added.…”
Section: Design Strategies Of Aie-type Metal Ncsmentioning
confidence: 99%
“…They showed that the key factors affecting the device performance were the concentration of metal NCs and the degree of zeolite anode contact. Last year, Li and coworkers introduced aggregation-enhanced Cu 3 (L 2 ) 3 (L 2 = 4-hexyl-3,5-dimethyl-1Hpyrazole) acting as an emissive layer into OLEDs [ 29 ], where the OLED exhibited red emission centering at 610 nm, with a current efficiency (of 7.21 cd/A), a luminance (1200 cd/m 2 ), as well as EQE (4%).…”
Section: Applications Of Aie-type Metal Ncsmentioning
confidence: 99%
“…35 Pyrazolate-based Cu(I) cyclic trinuclear complexes (CTCs) represent an important class in the family of coinage-metalbased CTCs, whose fascinating luminescence behaviors are often dominated by aggregation. 11,[36][37][38] Since 2003, 39 it has been well-documented that Cu(I) CTCs can show bright phosphorescence or changeable phosphorescence colours or intensities upon the formation of an excimer, exciplex, ground-state supramolecular polymer or adduct during aggregation. 11 The nine-membered Cu 3 N 6 coordination rings of Cu 3 pyrazolate 3 (Cu 3 Pz 3 ), providing Lewis acidic sites, π-acidic/basic sites, metal-metal interacting sites and low-lying intramolecular Cu⋯Cu excited states, often play an essential role in the abundant emissive properties, including photoluminescence (PL) thermochromism, mechanochromism, vapochromism, solvatochromism and concentration luminochromism.…”
Section: Introductionmentioning
confidence: 99%